If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -1d = 4 Solving 10 + -1d = 4 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -1d = 4 + -10 Combine like terms: 10 + -10 = 0 0 + -1d = 4 + -10 -1d = 4 + -10 Combine like terms: 4 + -10 = -6 -1d = -6 Divide each side by '-1'. d = 6 Simplifying d = 6
| 12b+3b-6b-8b-1=15 | | 7log(3x)+3log(5x)=5 | | 7h-35=95 | | 10s-12s+3s=-6 | | -20a+12a+11a=9 | | 10=3(y+2)+1 | | 10c-7c=18 | | 4z^10+6=1 | | 3(k-7)+2=8 | | 4z+5z=12+42 | | 19z+47=185 | | 2+3z=11 | | -4y+3b+8y+8b= | | 17x+17=4(4x+4) | | P=2a+2l | | 2w+4=6 | | -18k-2k+-8=8 | | x^2-2x-3/x^2-81 | | 5g+4=94 | | 4=16-2b | | 3t+2tb= | | 4*-1-3= | | -6(z+2)+3(4z-3)=5(z-3)+12 | | 6xy(-3)+12(-3x+2xy)-17= | | 98=7(r+3) | | 6=y+12 | | 2cosx-cosx=0 | | 5(1-x)(1-x)-6(x*x-3x-7)=x(x-3)-2x(x+5)-2 | | G-80/4=3 | | 12-3x=-4(6x+4)-4(-5-5x) | | 90=3(b-37) | | -.95(20)+0.80x=0.30(20+x) |